2005
DOI: 10.1007/s10640-005-6030-6
|View full text |Cite
|
Sign up to set email alerts
|

The Willingness to Accept Value of Statistical Life Relative to the Willingness to Pay Value: Evidence and Policy Implications

Abstract: Large disparities between willingness to accept (WTA) and willingness to pay (WTP) based values of statistical life are commonly encountered in empirical studies. Standard economic theory suggests that if a public good is easily substitutable there should be no marked disparity between WTA and WTP values for the good, though the disparity increases with reduced substitutability. However, psychologists have shown that people often treat gains and losses asymmetrically and tend to require a substantially larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…WTAC for risk increases is expected to be higher than WTP for a similar risk reduction, because people do not have to consider their budget constraint and the potential presence of an endowment effect under WTAC (e.g. Guria et al 2005). Since WTAC questions are concerned with increases in risk, absolute changes in risk levels are used in the analysis.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…WTAC for risk increases is expected to be higher than WTP for a similar risk reduction, because people do not have to consider their budget constraint and the potential presence of an endowment effect under WTAC (e.g. Guria et al 2005). Since WTAC questions are concerned with increases in risk, absolute changes in risk levels are used in the analysis.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…Theoretically, the values of WTP and WTA should not differ greatly [51], however, in practice, large divergences between WTP and WTA can be observed due to factors such as substitutability, income effect and transaction costs) [20,50,52,53]. In most cases, WTP estimates are used, as they are more conservative [3,49].…”
Section: Choice Of Willingness To Acceptmentioning
confidence: 99%
“…In most cases, WTP estimates are used, as they are more conservative [3,49]. Nonetheless, a number of empirical studies in a variety of circumstances have found that WTA is more reliable, especially for environment or ecosystem management [52,53]. In particular, an ecosystem or landscape restoration programs are designed to restore degrading ecosystems to prior healthy levels and thereby address perceived welfare losses.…”
Section: Choice Of Willingness To Acceptmentioning
confidence: 99%
“…6 There are other studies reporting WTP-WTA disparity in the context of health and value of life. Examples include hearing aid provision (Grutters et al 2008), new medicine (O'Brien et al 1998), health risk from drinking water (Viscusi and Huber, 2012) and transport safety (Guria et al 2005). 6 values are higher than the true value, resulting in a WTP-WTA divergence that increases in uncertainties about the true value of the good being traded.…”
Section: Discrete Quantity Changes and Substitution Effectsmentioning
confidence: 99%